La actividad financiera de la unión europea: presupuesto y perspectivas financieras 2007-2013 - Langa Mora, Enrique; Valbuena Reyero, M.ª Rosario (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2006)
The aim of this paper is to present a short description of the financial activity of the European Union from the point of view of its budget. For this purpose, the budget historic evolution and its main characteristics are considered, as well as the financial perspectives during the period 2007-2013 when new members will join the European Union. Finally, the possible influence on the Spanish economy is also discussed.